KIAI'S SITUATIONAL LEADERSHIP STYLE IN FOSTERING SANTRI SPIRITUAL INTELLIGENCE - Muflihah, Ety; Trisnamansyah, Sutaryat; Sauri, Sofyan; Hanafiah, Hanafiah (Jurnal JOEPALLT (Journal of English Pedagogy, Linguistics, Literature, and Teaching), 2021)
The existence of a kiai as the leader of the pesantren is very decisive in the activities of mobilizing or motivating the members of the pesantren he leads, the kiai must be able to take actions that are always directed at achieving the goals of the pesantren organization. From here comes a leadership style that must be used as an appropriate strategy for running a pesantren organization, especially in terms of fostering the spiritual intelligence of its students. The Spiritual Intelligence (SQ) that must be possessed by students is the intelligence to place the attitudes and behavior of students who are able to implement and practice the knowledge of religion and the values contained in religion in accordance with Allah's orders and the Example of Rosululloh SAW. Spiritual intelligence (SQ) is needed to judge that one's actions or way of life are more meaningful than others. One of the leadership models that can be adopted by kiai is situational leadership whose implementation is tailored to the situation at hand. Hersey and Blanchard (1982: 180) say "there is no one best way to influence people's behavior, which leadership style a person will apply to people or groups of people depending on the level of maturity of the people who will be influenced by the leader." . Furthermore, Hersey and Blanchard (1982: 180) explain the level of maturity of those who are led to give rise to four leadership styles, namely: telling (telling), selling (selling), participating, delegating (delegating). Referring to the leadership model above, using a descriptive qualitative approach, the researcher conducted research on Kiai's Situational Leadership in Fostering the Spiritual Intelligence of the Santri. Case Studies at Daarul Mughni Al-Maaliki Islamic Boarding School Bogor and At-Tawaazun Islamic Boarding School Subang, West Java.